2004
DOI: 10.1111/j.1399-3011.2004.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐point mutations at the surface of MB‐1Trp lead to important changes in its conformational properties

Abstract: Protein design is currently used for the creation of new proteins with desirable traits. In our lab we focus on the synthesis of proteins with high essential amino acid content having potential applications in animal nutrition. One of the limitations we face in this endeavour is achieving stable proteins despite a highly biased amino acid content. We report here the synthesis and the characterization of three variants of MB-1Trp in which two solvent-exposed Leu have been replaced by Glu allowing for the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Further improvement of the folding and stability of the MB‐1 protein has been reported that should result in increased accumulation of the protein in the production host. Efforts to improve MB‐1 stability have considered several potential contributing factors: core packing (Gagnon et al ., 2000), helix ‘capping’ (Parker and Hefford, 1998), loop optimization (Simons et al ., 2001), addition of salt bridges (Sasseville et al ., 2004) and addition of disulphide bridges (Doucet et al ., 2002). Some of these projects have resulted in substantial improvement in the properties of MB‐1 as a potential nutritive protein.…”
Section: Engineering Novel Proteins As Sources Of Eaasmentioning
confidence: 99%
“…Further improvement of the folding and stability of the MB‐1 protein has been reported that should result in increased accumulation of the protein in the production host. Efforts to improve MB‐1 stability have considered several potential contributing factors: core packing (Gagnon et al ., 2000), helix ‘capping’ (Parker and Hefford, 1998), loop optimization (Simons et al ., 2001), addition of salt bridges (Sasseville et al ., 2004) and addition of disulphide bridges (Doucet et al ., 2002). Some of these projects have resulted in substantial improvement in the properties of MB‐1 as a potential nutritive protein.…”
Section: Engineering Novel Proteins As Sources Of Eaasmentioning
confidence: 99%